Sub-GeV millicharge dark matter from the U(1) X hidden sector - Feng, Wan-Zhe; Zhang, Zi-Hui; Zhang, Kai-Yu (Journal of cosmology and astroparticle physics, 2024)
We conduct a comprehensive study on the sub-GeV millicharge dark matter produced through the freeze-in mechanism. We discuss in general the mixing mechanism, encompassing both kinetic mixing and mass mixing, between the U(1) X hidden sector and the standard model, which can generate millicharge carried by the dark fermions from the hidden sector. We discuss in depth how such millicharge is generated, and clarify several misunderstandings regarding this subject in the literature. Without employing an effective field theory approach, where the photon field directly mixed with the additional U(1), we analyze a general renormalizable model and investigate the complete evolution of the hidden sector particles. Due to the substantial self-interactions among hidden sector particles, the evolution of the hidden sector temperature plays a crucial role, which is addressed concurrently with the number densities of hidden sector particles by solving a set of coupled Boltzmann equations. We thoroughly examine eight benchmark models from six distinct cases. Some of our key findings from the analysis of these benchmark models may be generalizable and applicable to broader freeze-in scenarios. We also explore the possibility that the (keV) U(1) X dark photon is a viable dark matter candidate, even though it can contribute at most ∼ 5% to the total observed dark matter relic density.